MQTT Protocol for Efficient AI Communication - Khot, Suraj; Mali, Abhijeet (International Journal of Engineering and Management Research, 2024)
In recent years, advancements in Internet of Things (IoT) and artificial intelligence have revolutionized various fields, including biometric authentication systems. This project focuses on integrating IoT with face recognition technology to create a robust and efficient authentication system. The proposed system leverages MQTT (Message Queuing Telemetry Transport), a lightweight messaging protocol ideal for IoT environments, to facilitate real-time communication between face recognition devices and centralized software. The core of the system involves deploying face recognition devices equipped with cameras and processing units capable of capturing and analyzing facial features. These devices are subscribed to an MQTT broker, such as Mosquitto, enabling them to publish real-time data regarding recognized faces and authentication status. Simultaneously, a centralized software service, also subscribed to the MQTT broker, receives this data and provides a user interface for administrators to monitor and manage access control. Key functionalities include face detection, feature extraction, and matching against a database of enrolled faces. MQTT ensures low latency and efficient data transmission, crucial for real-time applications. The software component integrates MQTT client libraries to seamlessly interface with the MQTT broker, facilitating bi-directional communication between devices and the central server. The project aims to address security, scalability, and real-time performance challenges inherent in face recognition systems by harnessing the power of IoT and MQTT. By implementing this system, organizations can enhance security measures while simplifying access control processes through automated facial recognition technology.